Implementation of Rehabilitation for Narcotics Addicts in Positive Legal Perspective and Islamic Law - Analisa, Lisa; Kamarusdiana, Kamarusdiana; Adhha, Nurul (Al-Risalah, 2022)
This study aims to analyze the concept of rehabilitation of addicts at BABESREHAB BNN Lido West Java so that obstacles and challenges in the implementation of rehabilitation for narcotics addicts can be identified with the help of empirical normative analysis. This research also aims to analyze the actualization – in social rehabilitation, especially the mental coaching room. This research was a legal research with an interdisciplinary socio-legal study. The author uses this study model in order to describe legal issues more meaningfully from both a theoretical and practical point of view. This research was conducted at the Rehabilitation Center of the National Narcotics Agency (BABESREHAB BNN Lido West Java) Lido because this rehabilitation institution is a large rehabilitation center directly owned by the government, which was suspected to have made a major contribution to the success of rehabilitation in accordance with applicable laws and policies. This study also uses a mixed methodology consisting of reviewing legal documents and government policies and institutions under it, focus group discussions, and semi-structured interviews. This study also uses an ethnographic content analysis approach known as Ethnographic Content Analysis (ECA). Research informants consisted of 7 practitioner staff and 4 informants from rehabilitation residents. This study concludes that rehabilitation in Indonesia still requires attention from all parties, government, private, and family in solving all obstacles and challenges in its implementation. The allegation that the Lido National Narcotics Agency Rehabilitation (BABESREHAB BNN Lido West Java) which is directly controlled by the government, has contributed greatly to the success of rehabilitation in accordance with the law, applicable policy, as well as - not yet fully confirmed. This study found several problems in the implementation of rehabilitation, namely, (1) there is no reach out for prospective rehabilitation residents, (2) there are still dilemmas in forced rehabilitation, resident motivation, and vocational training (3) limited number of functional personnel, (4) lack of awareness legal and policy context, (5) Islamic mental development curriculum is not yet comprehensive.